Whole core analysis of the single-fluid double-zone thorium molten salt reactor (SD-TMSR). (March 2020) - Ashraf, O.; Rykhlevskii, Andrei; Tikhomirov, G.V.; Huff, Kathryn D.
Highlights: Sixty years of depletion and fuel processing in a SD-TMSR is simulated using SERPENT-2 to find the equilibrium fuel composition. The feed rates of 232 Th and 233 U required for reactor criticality are determined. Breeding ratio, net production of fissile 233 U and doubling time are estimated and validated. Benefits of online fission product removal in the SD-TMSR are identified. Temperature coefficient of reactivity evolution during SD-TMSR operation are investigated. Abstract: The SD-TMSR (2, 250 MW th ) is a Single-fluid Double-zone Thorium-based Molten Salt Reactor. The active core of the SD-TMSR is divided into the inner zone (486 fuel tubes) and the outer zone (522 fuel tubes) to improve the Th-U3 breeding performance. This work adopted the SERPENT-2 Monte Carlo code to analyze the whole core model of the SD-TMSR. Built-in SERPENT-2 capabilities simulated online reprocessing and refueling and calculated the multiplication factor and Breeding Ratio (BR). We found that the molten salt Temperature Coefficient of Reactivity ( α T ) was negative for initial and equilibrium states. This study investigated the variation of the multiplication factor, BR, and build-up of important nuclides in the core as a function of burnup. Under online reprocessing and refueling, we studied the variation of the reactivity during 60 years of reactor operation. Additionally, the neutron spectrum shift during the reactor operation was calculated. Finally, these simulations determined the appropriate 232 Th and 233 U feed rates for maintaining criticality and enabled analysis of the overall SD-TMSR fuel cycle performance.